THE STRONG C-SYMMETRICAL DISTRIBUTION - Ranga, A. S. (Australian Mathematics Publ Associação Inc, 1992)
In this paper, we consider a class of strong symmetric distributions, which we refer to as the strong c-symmetric distributions. We provide, as the main result of this paper, conditions satisfied by the recurrence relations of certain polynomials associated with these distributions.